Introduction to the American economy - "Graft - Johnson, J C De" (Bombay, 1962)
This book is an authoritative introduction to African economy. To begin with the author discusses the problem of growing population in relation to food supply. This is followed by an analysis of the indigenous system of land tenure and their impact on overall production.
Keywords: Economics